Let "y=y_1u" , hence "y'=y_1'u+y_1u'" , and "y''= y_1''u+2y_1'u'+y_1u''".
Then
"0=4x^2 y''+y=4x^2 (y_1''u+2y_1'u'+y_1u'') +y_1u ="
"= 4x^2(2y_1'u'+y_1u'')+(4x^2y_1''+y_1)u=4x^2(2y_1'u'+y_1u'')", since "4x^2y_1''+y_1=0".
"2y_1'u'+y_1u''=0"
"2y_1'y_1u'+y_1^2u''=(y_1^2u')'=0"
"y_1^2u'=C_1"
"u'=C_1\/y_1^2"
"u=\\int\\frac{C_1dx}{x\\ln^2 x} =C_0 - C_1\\frac{1}{\\ln x}"
"y=y_1u=(C_0 - C_1\\frac{1}{\\ln x})\\sqrt{x}\\ln x=C_0\\sqrt{x}\\ln x-C_1\\sqrt{x}" is the general solution.
The functions "y_1(x)=\\sqrt{x}\\ln x", "y_2(x)=\\sqrt{x}" are linearly independent. Indeed, if
"a_1y_1+a_2y_2= 0" , then "a_1\\ln x+a_2=0" . Since "a_1\\ln x=-a_2" is a constant, "a_1=0" and hence "a_2=0". This means that "y_1(x)" and "y_2(x)" are linearly independent.
The functions "y_1(x)" and "y_2(x)" form a fundamental set of solutions, since they are linear independent, and the general solution is their arbitrary linear combination.
Comments
Leave a comment